Increasing the reading ability of a student with dyslexia in elementary school: an explanatory case study by using family support, remedial teaching, and multisensory method - Tarjiah, Indina; Supena, Asep; Pujiastuti, Sri Indah; Mulyawati, Yuli (Frontiers in Education, 2023)
Dyslexia is a neurodevelopmental disorder that may lead to difficulties in reading and other language-related cognitive processes. Approximately 5% to 10% of students in public schools have this disorder, which requires specific learning strategies to improve their reading abilities. Therefore, this study aimed to explore the successful experiences of teachers in improving the reading ability of a student with dyslexia. To achieve this, a qualitative approach was used, with an explanatory case study method conducted in a public inclusive Elementary School located in Bogor City, Indonesia . This particular school was selected due to the presence of dyslexia and experienced teachers in handling students with disabilities. The participants comprised of four individuals, including a 3rd-grade student diagnosed with dyslexia, an experienced teacher, an assistant teacher, and parents of the diagnosed student. Furthermore, interviews were conducted with classroom teachers and the assistant, as well as parents. Document analysis and four-time classroom observation were also carried out to support the data. The result showed that there were four key factors in determining the success of reading in a student with dyslexia, namely (1) remedial teaching, (2) application of multisensory methods, (3) reading media use, and (4) parental support. It provided valuable insights for teachers dealing with the students with dyslexia, in order to improve their reading skills while considering the specific needs.